(untitled) (Malaysian Management Journal, 1992)
Shareholders are basically owners of their corporations who elect corporate directors (who are policy makers) and employed corporate management (who implement corporate policies). In modern. businesses, due to the large number and dispersion of shareholders, control is normally vested to professional managers who may pursue actions in their own self-interest rather than those of the shareholders. This paper reviews various ways managers are perceived to deviate from the shareholders’ wealth maximisation objective, and the possible methods and constraints involved of aligning management’s and shareholders’ interests. In the final analysis, the long-term survival of the firm and the management depends upon the management’s actions being congruous with shareholders’ interest.